MODELING AND OPTIMIZATION OF WEIGHT-MEASURING SYSTEM FOR CONTINUOUS DOZING OF DRY MATERIALS - Koshevoy, N. D.; Kalashnikov, Е. Е.; Kostenko, Е. М.; Cherepashchuk, G. A. (Radio Electronics, Computer Science, Control, 2010)
In this article the mathematical models of a weight measuring system have been developed with the use of optimum price expenses experiment planning. The optimum modes of its operation have been determined.